2018
DOI: 10.1038/s41550-018-0551-8
|View full text |Cite
|
Sign up to set email alerts
|

The inside-out planetary nebula around a born-again star

Abstract: Planetary nebulae are ionized clouds of gas formed by the hydrogen-rich envelopes of low-and intermediate-mass stars ejected at late evolutionary stages. The strong UV flux from their central stars causes a highly stratified ionization structure, with species of higher ionization potential closer to the star. Here we report on the exceptional case of HuBi 1, a double-shell planetary nebula whose inner shell presents emission from low-ionization species close to the star and emission from high-ionization specie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(86 citation statements)
references
References 32 publications
19
67
0
Order By: Relevance
“…Stellar evolution models are predicted to slow their evolution as they reach their maximum effective temperature (i.e. the knee of the evolutionary tracks in the HR-diagram, see the supplementary material in Guerrero et al 2018). Alternatively, this could be a consequence of the larger luminosity expected during the earlier stellar evolution, which leads to a larger volume in which these stars can be detected.…”
Section: Dichotomy Between H Rich and Poor Cspnementioning
confidence: 99%
“…Stellar evolution models are predicted to slow their evolution as they reach their maximum effective temperature (i.e. the knee of the evolutionary tracks in the HR-diagram, see the supplementary material in Guerrero et al 2018). Alternatively, this could be a consequence of the larger luminosity expected during the earlier stellar evolution, which leads to a larger volume in which these stars can be detected.…”
Section: Dichotomy Between H Rich and Poor Cspnementioning
confidence: 99%
“…A priori one would expect little if any difference in the DA and non-DA IFMRs. The (V)LTP channel for production of non-DA WDs does not appear to result in significant mass loss from the evolving stellar core (e.g., Clayton et al 2013;Guerrero et al 2018;Evans et al 2020;Schaefer et al 2020). Empirically, the mean masses and overall mass distribution of field DA and non-DA WDs are observed to be very similar (spectroscopic mean masses of 0.615 M for DAs and 0.625 M for DBs; Genest-Beaulieu & Bergeron 2019b), though the DA distribution has a more substantial high-mass tail and a secondary peak at low mass due to binary star evolution (e.g., Bergeron et al 1992;Falcon et al 2010Falcon et al , 2012Kleinman et al 2013;Genest-Beaulieu & Bergeron 2019a).…”
Section: The Initial-final Mass Relationmentioning
confidence: 99%
“…Lau et al 2011;Clayton et al 2013), while FG Sge (e.g., Gonzalez et al 1998;Lawlor & MacDonald 2003) and V839 Aql (e.g., Parthasarathy et al 1993;Reindl et al 2014Reindl et al , 2017 are classified as likely LTPs. These thermal pulses do drive some additional mass loss; the ejected gas mass is measured at ∼ 10 −5 − 10 −4 M based on observations of ejecta in known (V)LTP events and in H-deficient planetary nebulae (e.g., Clayton et al 2013;Guerrero et al 2018;Evans et al 2020;Schaefer et al 2020). These thermal pulses send the star back toward the AGB in the Hertzsprung-Russell diagram, and total mass loss in the renewed post-AGB phase may approach to ∼ 10 −2 M (Althaus et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have presented stark evidence of the dramatic changes experienced by the CSPN of born-again PNe (see, e.g., the case of the Sakurai's Object; Evans et al 2020), and in particular HuBi 1. Guerrero et al (2018) demonstrated that in less than 50 yr its CSPN declined its brightness in about 10 mag changing its atmosphere and, as a consequence, producing changes in the ionization structure of its surrounding PN.…”
Section: Introductionmentioning
confidence: 99%
“…1). The outer shell with an angular radius of 𝑟 ∼ 8 is dominated by emission from recombination lines of H and He , whilst its inner shell with 𝑟 ∼ 2 is dominated by emission from forbidden lines (Guerrero et al 2018). The inner shell has a notable inverted ionization structure, with ★ E-mail: j.toala@irya.unam.mx the emission from higher ionization species such as O ++ and He ++ encompassing that from lower ionization species such as N + , O + and S + (Guerrero et al 2018, Montoro-Molina et al, in preparation).…”
Section: Introductionmentioning
confidence: 99%